Predicting COVID-19 vaccination intention: the determinants of vaccine hesitancy - Fernandes, Nuno (2021)
Data is available at https://doi.org/10.17605/OSF.IO/TR2P3. Analysis code was written in R and Python and is available at https://nunokf.github.io/Predicting-COVID-19-Vaccination-Intention-The-Determinants-of-Vaccine-Hesitancy-/.